1n(5x+3)=3.6

Simple and best practice solution for 1n(5x+3)=3.6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1n(5x+3)=3.6 equation:


Simplifying
1n(5x + 3) = 3.6

Reorder the terms:
1n(3 + 5x) = 3.6
(3 * 1n + 5x * 1n) = 3.6
(3n + 5nx) = 3.6

Solving
3n + 5nx = 3.6

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Reorder the terms:
-3.6 + 3n + 5nx = 3.6 + -3.6

Combine like terms: 3.6 + -3.6 = 0.0
-3.6 + 3n + 5nx = 0.0

The solution to this equation could not be determined.

See similar equations:

| 42+x+y=180 | | h(-1)=2x^2+4 | | h(0)=2x^2+4 | | 3x+3y=x-2y | | -3z-9z=4/5 | | a^2-2ab+b^2+4a^2b^2=0 | | h(2b)=2x^2+4 | | 18x-24x=1/3 | | 7=-5x+10 | | 4=5d+14 | | 4x+16y=7x+y | | x^2-216= | | 5w+3+w= | | 3/4*3*5 | | an=-2+(n-1) | | y=x^2-5x-9 | | 7x+y=4x+16y | | 5d^2-10d+h=0 | | (y^4/-2z^2)^4 | | X^2+15x+56.25=26.25 | | 5x-5x=200 | | 9=26+3 | | 4-11=17 | | 6f=6f-24 | | g^2-12gh+35h^2=0 | | 5x-25+x+13=180 | | C=4-3X-4Y+2X^2+3Y^2+XY | | logx^2-3logx=-2 | | d^2=490 | | 2b+3(3b+1)=52 | | -3/4x72 | | -4+24=-24 |

Equations solver categories